117 IS AKAP-4 A NOVEL CANCER TESTIS ANTIGEN FOR MULTIPLE MYELOMA?. Issue 1 (1st January 2007) - Ferrari, R.; Kelly, A.; Grizzi, F.; Yuefei, Y.; Cobos, E.; Chiriva-Internati, M.
Abstract : Purpose: Immunotherapy promises to be a more gentle and successful cancer treatment when compared with current standard treatments. Multiple myeloma (MM) is still a fatal hematologic malignancy that represents approximately 1% of all cancers and 2% of all cancer deaths. Approximately 50, 000 Americans currently have MM. The research to discover new suitable cancer targets is needed to improve the effects of immunotherapy. The AKAP family's protein provides an organizing center about which various protein kinases and phosphatases can be assembled to create solid-state signaling devices that can signal, be modulated, and be trafficked within the cell. A member of this family, AKAP-4, is the focus of our study. Human AKAP-4 is a structural protein of the sperm fibrous sheath that also functions to anchor protein kinase A to this structure via the regulatory subunit of the kinase, and seems to be involved in sperm motility. Our aim was to investigate the presence of AKAP-4 as a novel cancer testis antigen target in MM patients. Methods: We evaluated the expression of AKAP-4 mRNA in a normal panel of tissues and in 15 MM patients either by PCR and immunocytochemistry. The normal control investigated tissues were kidney, ovary, skeletal muscle, mammary, brain, heart, colon, stomach, liver, lung, pancreas, spleen, trachea, and bone marrow. Summary: The analysis of the mRNA expression of AKAP-4 showed that none of the normal tissues produced any positive band signals, whereas 6 of the 15 investigated patients (40%) showed a positive band signal. The immunohistochemical approach to the normal tissue panel showed no staining in any of the evaluated organs, except for the control, the testis. Five of the 15 MM investigated cases (33.3%) showed positive cytoplasmic staining. Conclusion: To our knowledge, we established for the first time that AKAP-4 is expressed at the transcriptional level in MM cases, with a rate of 40%, whereas it is not expressed in normal tissues. Immunocytochemical data confirmed the PCR observations even if with a slightly lower percentage rate (33.3%). Since AKAP-4 has yet not been studied in MM, this is the first study that gives evidence of its aberrant expression in MM and suggests its use as possible novel cancer testis antigen target in MM.